2014
DOI: 10.1007/s00438-014-0884-7
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA haplogroup D4b is a protective factor for ischemic stroke in Chinese Han population

Abstract: Mitochondrial DNA (mtDNA) haplogroups affect the assembly and stability of the mitochondrial respiratory chain, which is potentially related to susceptibility to ischemic stroke (IS). However, the role of mtDNA in IS has not been comprehensively studied. The purpose of this study was to explore whether mtDNA polymorphisms and haplogroups are involved in the etiology of IS in the Chinese Han population. We recruited 200 patients with IS and 200 matched controls and genotyped them for 18 mtDNA single nucleotide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The relationship between mtDNA haplogroup and ischemic stroke has been studied with inconclusive results. Mitochondrial DNA haplogroup K and H1 have been identified as protective factors in the European population (OR = 0.54 and OR = 0.61, respectively) [ 6 , 7 ], while mtDNA haplogroup D4b was found to be protective in Han Chinese patients (OR = 0.028) [ 8 ]. Recently, mtDNA haplogroup N9 was reported as an independent protective factor against neurological worsening in acute ischemic stroke patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between mtDNA haplogroup and ischemic stroke has been studied with inconclusive results. Mitochondrial DNA haplogroup K and H1 have been identified as protective factors in the European population (OR = 0.54 and OR = 0.61, respectively) [ 6 , 7 ], while mtDNA haplogroup D4b was found to be protective in Han Chinese patients (OR = 0.028) [ 8 ]. Recently, mtDNA haplogroup N9 was reported as an independent protective factor against neurological worsening in acute ischemic stroke patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, these Caucasian haplogroups present rarely in Asian population, and therefore their effects could not be evaluated in this study. Mitochondrial haplogroup D4b was also reported as a protective factor against ischemic stroke in Han Chinese population 33 . But the frequency of haplogroup D4b is very low in patients enrolled in this study; its association was not tested.…”
Section: Discussionmentioning
confidence: 96%
“…Stroke is a complex multifactorial disorder caused by both genetics and environment in the Chinese population (Della-Morte et al, 2012). One study shows that mtDNA C5178A belongs to haplogroup D4b and is a protective factor for IS in the Chinese Han population ( n = 200) (Yang et al, 2014). Other studies reported that m.5178C, but not m.5178A, is a risk factor for several diseases including myocardial infarction ( n = 517), cerebrovascular diseases ( n = 127), and diabetes ( n = 270) (Wang et al, 2001; Ohkubo et al, 2002; Takagi et al, 2004).…”
Section: Mitochondrial Haplogroups Associated With Disease In East Asiamentioning
confidence: 99%